The Influence of Gender Mainstreaming on the Sustainability of Cooperative Movement among General Multipurpose Cooperative Societies of Tertiary Institutions in Ekiti State, Nigeria - Ajayi, Ibidolapo Ezekiel (Management Science Research Journal, 2024)
The study examined General Multipurpose Cooperative Societies at Tertiary Institutions in Ekiti State, Nigeria, to see how gender mainstreaming affects their long-term viability. This research examines how gender empowerment, affirmative actions, and project committee participation affect cooperative movement sustainability. The research population includes 2,577 Ekiti State university multipurpose cooperative society members. The sample included 346 members of three Ekiti State university general cooperative societies. Multiple regression and frequency tables were used to examine the data for the investigation. The research found that gender mainstreaming considerably impacts the Ekiti State cooperative movement. The study shows that gender mainstreaming benefits the contemporary cooperative movement. Reason being, cooperative movement participants are more likely to display initiative, self-confidence, and involvement. The report recommends gender mainstreaming in cooperative policies and activities to promote long-term viability. We must adopt long-term gender equality tactics, eradicate gender-based obstacles, and provide women and men equal agency in decision-making and cooperative endeavours to attain this aim.